A case report on hydroquinone induced exogenous ochronosis - Sunkara, Hari Priya; Kilaru, Krishna Rajesh; Kumar, Adusumilli Pramod; Ramineni, Hari Babu; Krishna, Puvvada Rahul (International Journal of Advances in Medicine, 2020)
Exogenous ochronosis is an infrequent skin disorder characterised by bluish-black or grayish brown pigmentation on dermis. It is the most common condition caused due to long term application of Hydroquinone skin preparations for melasma, skin brightening, cholasma, acne induced pigmentation etc. This report refers to a case of 39-year-old female patient who presented to the hospital with chief complaints of progressive formation of dark lesions over face, neck since one and half-year. She had history of usage of hydroquinone (4%) cream for skin brightening for a period of three months. Based on clinical findings and history she was diagnosed to have acquired exogenous ochronosis and was treated with microdermabrasion, cosmelan peel, yellow peel, glutathione tablets, topical sunscreen and kojic acid cream. Patient noted 50% improvement in her condition after 4 months of treatment. It is believed that application of high concentrations of hydroquinone for a prolonged period causes exogenous ochronosis. This case report suggests that exogenous ochronosis can occur after three months of application.